SOSIALISASI, EDUKASI SERTA BAKTI SOSIAL DALAM GERAKAN PESISIR BEBAS SAMPAH PLASTIK DI PANTAI NAGA PERMAI GAMPONG SUAK PUNTONG KECAMATAN KUALA PESISIR KABUPATEN NAGAN RAYA - Nabil Zurba; Yulie Rahayu Fitrianingsih; Muhammad Arif Nasution; Neneng Marlian (Universitas Teuku Umar, 2020)
One of the most visited attractions in Nagan Raya Regency is the Naga Permai beach area. Beautiful natural panorama makes the Naga Permai beach area has a tourist attraction. The high number of tourists visiting the Naga Permai beach area can have a negative impact in the form of tourism waste in the form of plastic waste which has the potential to reduce the environmental quality and environmental sustainability of the Naga Permai beach area. Tourism waste in the form of plastic waste from tourist activities sourced from tourists and tourism businesses. Purpose This activity is providing socialization. Socializing the importance of managing waste properly, sorting out plastic and non-plastic waste, as well as providing an overview of the consequences that will arise in the future if plastic waste is not controlled, and providing direct examples to the community on how to sort out garbage and exemplify so as not to dispose of waste when traveled. This service will be done using the approach method with the lecture / accompaniment method. While the stages to solve these problems by doing examples of social service. The output obtained is the emergence of awareness and initiative from café owners and visitors so as not to litter plastic.